Galactosylated Polymer/Gold Nanorods Nanocomposites for Sustained and Pulsed Chemo-Photothermal Treatments of Hepatocarcinoma - Gaetano Giammona; Salvatore Emanuele Drago; Giovanna Calabrese; Paola Varvarà; Maria Giovanna Rizzo; Nicolò Mauro; Giuseppe Nicotra; Sabrina Conoci; Giovanna Pitarresi (MDPI AG, 2022)
In this paper, we propose a rational design of a hybrid nanosystem capable of locally delivering a high amount of hydrophobic anticancer drugs (sorafenib or lenvatinib) and heat (hyperthermia) in a remote-controlled manner. We combined in a unique nanosystem the excellent NIR photothermal conversion of gold nanorods (AuNRs) with the ability of a specially designed galactosylated amphiphilic graft copolymer (PHEA-g-BIB-pButMA-g-PEG-GAL) able to recognize hepatic cells overexpressing the asialoglycoprotein receptor (ASGPR) on their membranes, thus giving rise to a smart composite nanosystem for the NIR-triggered chemo-phototherapy of hepatocarcinoma. In order to allow the internalization of AuNRs in the hydrophobic core of polymeric nanoparticles, AuNRs were coated with a thiolated fatty acid (12-mercaptododecanoic acid). The drug-loaded hybrid nanoparticles were prepared by the nanoprecipitation method, obtaining nanoparticles of about 200 nm and drug loadings of 9.0 and 5.4% w/w for sorafenib and lenvatinib, respectively. These multifunctional nanosystems have shown to convert NIR radiation into heat and release charged drugs in a remote-controlled manner. Then, the biocompatibility and synergistic effects of a chemo-phototherapy combination, as well the receptor-mediated internalization, were evaluated by an in vitro test on HepG2, HuH7, and NHDF. The results indicate that the proposed nanoparticles can be considered to be virtuous candidates for an efficient and selective dual-mode therapy of hepatocarcinoma.